SISTEM PENDUKUNG KEPUTUSAN PEMBENTUKAN BADAN ADHOC PADA KPU KOTAWARINGIN TIMUR MENGUNAKAN METODE AHP DAN TOPSIS - Andre Giofani; Depi Rusda (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2022)
Abstract: Decision support system is a system designed specifically for the decision-making process. Many agencies that have started using it from a small or large scale in carrying out recruitment activities have begun to make decisions by using the decision support system method to assist decision making. The decision support system for forming the ad hoc body at the kpu is a new breakthrough in determining the decision making to select prospective participants for the ad hoc agency to be more effective and efficient. At the time of the election stage, the KPU was often chased by the time stages that took place, such as the formation of the Adhoc body. The agency is trying to determine the Adhoc committee committee that meets the qualifications in a fairly short time, so that the KPU will use various criteria to obtain committees that match the criteria and assessments in recruitment that are less transparent. From the problems that have been described, the authors propose the creation of a website-based Decision Support System application using the Analytical Hierarchy Process (AHP) and TOPSIS methods to carry out the selection process and determine the required committee candidates according to the criteria determined by the agency with faster results. by using the system.